High strain rate effect on tensile ductility and fracture of AM fabricated Inconel 718 with voided microstructures. (October 2021) - Wood, P.; Rusinek, A.; Platek, P.; Janiszewski, J.; Sienkiewicz, J.; Gunputh, U.F.; Rajkowski, K.; Miguélez, M.H.
Graphical abstract: Highlights: New empirical model to predict porosity type and growth rates in Inconel718. Model used to optimise laser melting process for Inconel718. Electromagnetic Ring Expansion Tests on additively manufactured Inconel718. Significant strain rate effects on alloy ductility observed together with new trends. Abstract: The paper describes Electromagnetic Ring Expansion Tests (ERET) performed on Laser Melting Powder Bed Fusion (LPBF) Inconel 718 stress relieved test pieces, to establish the effect of a randomly dispersed spherically voided microstructure on tensile ductility, fracture, and fragmentation at high strain rate (10 −3  < ε < 10 4 s −1 ). An empirical model to predict porosity type and growth rates as a function of laser energy density was established, to select the LPBF process parameters to fabricate test pieces under stable conduction and keyhole melting. The size, shape, distribution of macro and keyhole pores in the test pieces obtained for ERET testing were characterised. At high strain rate the number of ring fragments for the highest porosity doubled, accompanied by a reduction in true strain at maximum uniform elongation and fracture strain. The trend for reducing fracture strain with increasing porosity at high strain rate was described by a decaying power law. Overall, there was a significant positive strain rate effect on tensile ductility at lower porosities attributed strain rate hardening (Hart, 1967) [1]. Fracture surfaces containing the highest porosity identified four different void coalescence mechanisms that helped explain the influence of larger pores on the stress state in the alloy.